2014
DOI: 10.1111/vco.12131
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin chemotherapy for presumptive cardiac hemangiosarcoma in dogs

Abstract: Sixty-four dogs were treated with single-agent doxorubicin (DOX) for presumptive cardiac hemangiosarcoma (cHSA). The objective response rate (CR + PR) was 41%, and the biologic response rate (CR + PR + SD), or clinical benefit, was 68%. The median progression-free survival (PFS) for treated dogs was 66 days. The median survival time (MST) for this group was 116 days and was significantly improved compared to a MST of 12 days for untreated control dogs (P = 0.0001). Biologic response was significantly associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 30 publications
3
29
0
Order By: Relevance
“…A recent larger study compared the outcome of 64 dogs with a presumptive diagnosis of cardiac HSA on echocardiography, treated with doxorubicin as a first line treatment, versus 76 untreated patients. Although median progression‐free survival (PFS) and MST were of short duration (66 and 119 days respectively) in those dogs receiving chemotherapy, the authors found an improved survival when compared to the untreated group, whose MST was 12 days only.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…A recent larger study compared the outcome of 64 dogs with a presumptive diagnosis of cardiac HSA on echocardiography, treated with doxorubicin as a first line treatment, versus 76 untreated patients. Although median progression‐free survival (PFS) and MST were of short duration (66 and 119 days respectively) in those dogs receiving chemotherapy, the authors found an improved survival when compared to the untreated group, whose MST was 12 days only.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Hemangiosarcoma (HSA) is an aggressive malignant cardiac tumor that is generally associated with a poor prognosis [1,9,11]. Surgical intervention (i.e., pericardiectomy with or without tumor removal) is performed for the purposes of diagnosis and prevention of cardiac tamponade rather than for curative intent or prolonged survival time because the median survival time is short (typically 5–6 months), even with surgical resection of the tumor followed by adjunctive chemotherapy [8,11].…”
Section: Discussionmentioning
confidence: 99%
“…It is the most common type of malignant cardiac tumor in dogs, accounting for approximately 70% of cardiac neoplasms in dogs [1,2]. Although cardiac tumors can be seen in any area within the heart (i.e., in the left ventricular free wall, in the interventricular septum or both) [3,4,5], the majority of primary cardiac hemangiosarcomas involve the right atrium or auricle [2,6,7,8,9]. Due to its highly invasive nature, the prognosis of cardiac hemangiosarcoma is reported to be poor with a reported median survival time (MST) of 7 days in non-treated dogs [8], between 42 days and 5 months in dogs with surgical removal of the tumor only [8,10,11], 139 days in dogs with chemotherapy only [12] and between 175 days and 189 days in dogs with surgical removal of the tumor and conventional chemotherapy [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…; Mullin et al . ). Reported survival times for pericardectomy alone was 52 days while mass resection alone or with chemotherapy resulted in a mean survival time of 46 and 164 days respectively (Kerstetter et al .…”
Section: Neoplasia‐related Emergenciesmentioning
confidence: 97%